Assessment of health-related quality of life (HRQoL) in patients with spasmodic dysphonia - Verma, Alok; Gupta, Babita; Agarwal, Saurabh (International Journal of Advances in Medicine, 2018)
Background: There is paucity of literature regarding health related quality of life in Spasmodic Dysphonia (SD) especially from India. This study assessed HRQoL in it’s global and disease specific aspect by previously validated instruments in patients with SD. Methods: The study was performed in AIIMS, New Delhi. Subjects with SD as well as age and gender matched healthy controls were enrolled from Movement Disorder and botulinum toxin clinic, Department of Neurology, AIIMS, New Delhi. Uneducated patient, those could not read questionnaires & cases who had received botulinum toxin within 6 months were excluded from the study. Each patient filled SF-36, BDI, VoiSS-30 and VPQ questionnaire. Results: 14 pts of Spasmodic Dysphonia (SD) were enrolled. Compared with controls SD patients suffered from statistically significant impaired global health related quality of life (SF36) in areas of role physical (p = 0.007), general health (p = 0.004), social functioning (p = 0.024), role emotion (p = 0.008) and mental health (p=0.039). Patients with SD scored much worse in BDI scale than their control group (12.57±8.0 vs. 4.71±5.0, p=0.005). 65% pt of SD had depression out of whom 14% had moderate depression. SD patient group showed statistically significant impaired scores in disease-specific QOL (VoISS) in 2 out of 3 subscales, impairment (p= <0.001) and emotional (p=<.001) but not in physical (p=0.44). Voice quality of patients with SD was severely affected compared to controls (mean 37± 8.0 vs. 12.9± 1.5). Conclusions: This study clearly demonstrated that patients with SD suffered from significant impairment in HRQoL as compared to controls. Higher proportion of patients with SD suffered from mild to moderate depression compared to their control.